2019
DOI: 10.1186/s12879-019-3801-1
|View full text |Cite|
|
Sign up to set email alerts
|

Nationwide epidemiology of carbapenem resistant Klebsiella pneumoniae isolates from Greek hospitals, with regards to plazomicin and aminoglycoside resistance

Abstract: Background To evaluate the in vitro activities of plazomicin and comparator aminoglycosides and elucidate the underlying aminoglycoside resistance mechanisms among carbapenemase-producing K. pneumoniae isolates collected during a nationwide surveillance study in Greek hospitals. Methods Three hundred single-patient carbapenemase-producing K. pneumoniae isolates were studied, including 200 KPC-, 50 NDM-, 21 VIM-, 14 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 27 publications
5
45
5
1
Order By: Relevance
“…All these resistance mechanism related factors explain the high variability of susceptibility rates to new β lactam based therapies against CRE. In addition, CRE are also often resistant to unrelated antibacterial classes, such as fluoroquinolones, aminoglycosides, fosfomycin and tigecycline, thus making them XDR and some times PDR 27 . Associated resistance to colistin and tigecycline is linked to worse clinical outcomes 28,29 .…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%
See 1 more Smart Citation
“…All these resistance mechanism related factors explain the high variability of susceptibility rates to new β lactam based therapies against CRE. In addition, CRE are also often resistant to unrelated antibacterial classes, such as fluoroquinolones, aminoglycosides, fosfomycin and tigecycline, thus making them XDR and some times PDR 27 . Associated resistance to colistin and tigecycline is linked to worse clinical outcomes 28,29 .…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%
“…Associated resistance to colistin and tigecycline is linked to worse clinical outcomes 28,29 . In Greece, prevalences of ~30% for XDR and ~5% for PDR have been reported 27 . The propensity for specific clones of K. pneumoniae to spread in hospital envi ronments has been shown to correlate with the degree of resistance; distressingly, carbapenemase producing isolates have the highest transmissibility 30,31 .…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%
“…Although most data available are for Klebsiella pneumoniae carbapenemase (KPC)-producing bacteria, in vitro data indicated that plazomicin had activity against some New Delhi metallo-b-lactamase (NDM)-producing organisms (80-92% susceptible), particularly when these isolates did not harbor the 16S rRNA methylase gene. [19][20][21] Plazomicin also has reduced or no activity against Enterococcus sp, Streptococcus sp, Acinetobacter sp, and Stenotrophomonas sp. 14 The drug has variable activity and higher minimum inhibitory concentrations (MICs) for 50% and 90% of isolates, respectively (MIC 50/90 ), to non-lactose-fermenting aerobic gram-negative pathogens including Morganella morganii, Proteus sp, and Pseudomonas sp.…”
Section: Chemistry and Pharmacologymentioning
confidence: 99%
“…Plazomicin (MIC 50/90 1/2 mg/L) inhibited 100% of the mcr-1 gene isolates at 2 mg/L or less and exhibited the most potent in vitro activity against colistinresistant Enterobacteriaceae, with an MIC 90 of 4 mg/L. 19,20,27,29,31,33,35 ≤ 0.5 1-2 ≤ 0.06 to > 128 CR-Enterobacteriaceae (n=1680) [19][20][21][28][29][30][31][32]34,35 0.25-1 1t o≥ 64 ≤ 0.06 to > 256 ESBL-producing Enterobacteriaceae (n=1261) 20,29,31,34,35 0.25-1 0.5-2 ≤ 0.06 to > 128 KPC-producing Enterobacteriaceae (n=267) 21,33,34 0.5 0.5 -AME producers (n=838) 20,27 0.5 2 16S RNA methylase producers (n=48) 20 > 128 > 128 E. coli (n=10,450) 19,20,23,25,29,31,[33][34][35] ≤ 0.5 to 2 1-2 ≤ 0.06 to > 128 Gent-R E. coli (n=288) 25 0.5 1 ≤ 0.12 to 2 Klebsiella pneumoniae (n=6680) 19,20,23,25,29,31,33,3...…”
Section: Chemistry and Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation